Can CT Virtual Cystoscopy Replace Conventional Cystoscopy in Early Detection of Bladder Cancer? - Abrol, Sachin (Adv Urol, 2015)
Aim. To correlate findings of conventional cystoscopy with CT virtual cystoscopy (CTVC) in detecting bladder tumors and to evaluate accuracy of virtual cystoscopy in early detection of bladder cancer. Material and Method. From June 2013 to June 2014, 50 patients (46 males, four females) with history and investigations suggestive of urothelial cancer, with mean age 62.76 ± 10.45 years, underwent CTVC by a radiologist as per protocol and subsequently underwent conventional cystoscopy (CPE) the same day or the next day. One urologist and one radiologist, blinded to the findings of conventional cystoscopy, independently interpreted the images, and any discrepant readings were resolved with consensus. Result. CTVC detected 23 out of 25 patients with bladder tumor(s) correctly. Two patients were falsely detected as negative while two were falsely labeled as positive in CTVC. Virtual and conventional cystoscopy were comparable in detection of tumor growth in urinary bladder. The sensitivity, specificity, positive predictive value, and negative predictive value of virtual cystoscopy were 92% each. Conclusion. CTVC correlates closely with the findings of conventional cystoscopy. Bladder should be adequately distended and devoid of urine at the time of procedure. However, more studies are required to define the role of virtual cystoscopy in routine clinical practice.